Development and application of a membrane assisted solvent extraction-molecularly imprinted polymer based passive sampler for monitoring of selected pharmaceuticals in surface water. (15th October 2022) - Khulu, Sinegugu; Ncube, Somandla; Nuapia, Yannick; Madikizela, Lawrence Mzukisi; Mavhunga, Elizabeth; Chimuka, Luke
Highlights: A novel MASE-MIP based passive sampler was developed for five pharmaceuticals An ionic liquid was utilized as a green receiver solution for the passive sampler Matrix-matched sampling rates achieved ranged from 0.0007 - 0.0018 L d −1 Only etilefrine (12.88 ng L −1 ) and methocarbamol (72.29 ng L −1 ) were quantified Other drugs were not detected with detection limits from 2.45 - 3.26 ng L −1 Abstract: In this work, we demonstrate the development, evaluation and pre-liminary application of a novel passive sampler for monitoring of selected pharmaceuticals in environmental waters. The samplers were calibrated in laboratory-based experiments to obtain sampling rates (Rs) for carbamazepine, methocarbamol, etilefrine, venlafaxine and nevirapine. Passive sampling was based on the diffusion of the target pharmaceuticals from surface water through a membrane bag which housed an ionic liquid as a green receiving solvent and a molecularly imprinted polymer. Effects of biofouling, deployment time and solvent type for the receiver phase were optimized for selective uptake of analytes in surface water. Notably, there was a decrease in the uptake of selected pharmaceuticals and consequently a decrease in their sampling rates in the presence of biofouling. The optimum matrix-matched sampling rates ranged from 0.0007 - 0.0018 L d −1 whilst the method detection and quantification limits ranged from 2.45 - 3.26 ng L −1 and 8.06 - 10.81 ng L −1, respectively. The optimized passive sampler was deployed in a dam situated in the heart of a typical highly populated township in the Gauteng Province of South Africa. Only etilefrine and methocarbamol were detected and quantified at maximum time weighted average concentrations of 12.88 and 72.29 ng L −1, respectively. Graphical abstract: Image, graphical abstract